The Spanish Connection French and Flemish Merchant Networks in Seville 1570-1650 - Crailsheim, Eberhard (2016)
In early modern times, the city of Seville was the most important entrepôt between the Old and the New World, attracting numerous merchants from all of Europe. They provided the American market with European merchandise, especially with textiles and metalware from Flanders and France. This book investigates the networks of Flemish and French merchants in Seville, displaying overall structures of trade as well as collective strategies of both merchant colonies.